2020
DOI: 10.15761/ifnm.1000282
|View full text |Cite
|
Sign up to set email alerts
|

Caramel dye IV increases hepatic and renal oxidative stress injuries

Abstract: Caramel dye IV (C-IV) is a synthetic organic product, does not present nutritional, ergogenic, or technological factors, but leads to reactive oxygen species (ROS). This way may lead to damage to a wide range of molecules, leading to cancer, cardiovascular, and neurodegenerative diseases development. We aimed to verify the effects of different doses of C-IV dye on the markers of oxidative stress in the liver and kidneys from male Swiss CF-1 mice, divided into four experimental groups: control; C-IV 0.3 g/kg; C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Similarly, kidneys of rats treated with high dose of sunset yellow (Figure B5) and both of low and high doses of (tartrazine + brilliant blue) (Figures B6 and B7) showed that some alterations including hypercellularity of the glomerular, narrowing of the urinary space, infract glomerulus, cellular infiltration and hypotrophy of the glomerulus. Similar histopathological effects were found in other studies by AL-Dahhan et al (2014); Ali et al (2016); Yadav et al (2017); Mohamed et al (2019) and Marins et al (2020).…”
Section: Histopathological Alterationssupporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, kidneys of rats treated with high dose of sunset yellow (Figure B5) and both of low and high doses of (tartrazine + brilliant blue) (Figures B6 and B7) showed that some alterations including hypercellularity of the glomerular, narrowing of the urinary space, infract glomerulus, cellular infiltration and hypotrophy of the glomerulus. Similar histopathological effects were found in other studies by AL-Dahhan et al (2014); Ali et al (2016); Yadav et al (2017); Mohamed et al (2019) and Marins et al (2020).…”
Section: Histopathological Alterationssupporting
confidence: 91%
“…Tawfek et al (2015) who found that highly significant increase in malondialdehyde, Glutathione Peroxidase and catalase activities in treated rats with sunset yellow and tartrazine. Marins et al (2020) found that administration of caramel IV dye in dose 3 g/kg b.w. induced oxidation damage in liver and kidney by increase of malondialdehyde and reduction of free SH group.…”
Section: Effect Of the Oral Administration Of Tested Colorants On Ant...mentioning
confidence: 99%
See 1 more Smart Citation